DESIGN OF A PERSONAL COMPUTER-BASED MEDICAL AND PHARMACEUTICAL PRODUCT INFORMATION RETRIEVAL SYSTEM - OKAMOTO, Hideki; YASUOKA, Toshiaki; KATO, Hiroyoshi; SUZUKI, Fumiyuki (Japanese Journal of National Medical Services, 1993)
As inquiries concerning medical and pharmaceutical information business become more sophisticated, the ability to exchange questions and answers in written format is becoming essential. As part of the efforts to construct the “Medical and pharmaceutical Information Network among National Medical Institutions through FAX”, a facsimile was installed in the Medical and Pharmaceutical Information Management Office in our Pharmaceutical Department, in July 1990. With this installation, it became possible to exchange medical and pharmaceutical information through written documents. The medical and pharmaceutical information retrieval system reported in this paper uses personal computers, along with a card-based database management system. This combination enables the proper storage, management, and indexing of medical and pharmaceutical documents, and thus increases the information collection capacity of the system.